Public Markets and Civic Culture in Nineteenth-Century America - Tangires, Helen (Johns Hopkins University Press, 2020)
Originally published in 2003. In Public Markets and Civic Culture in Nineteenth-Century America Helen Tangires examines the role of the public marketplace-social and architectural-as a key site in the development of civic culture in America. More than simply places for buying and selling food, Tangires explains, municipally owned and operated markets were the common ground where citizens and government struggled to define the shared values of the community. Public markets were vital to civic policy and reflected the profound belief in the moral economy-the effort on the part of the municipality to maintain the social and political health of its community by regulating the ethics of trade in the urban marketplace for food. Tangires begins with the social, architectural, and regulatory components of the public market in the early republic, when cities embraced this ancient system of urban food distribution. By midcentury, the legalization of butcher shops in New York City and the incorporation of market house companies in Pennsylvania challenged the system and hastened the deregulation of this public service. Some cities demolished their marketing facilities or loosened restrictions on the food trades in an effort to deal with the privatization movement. However, several decades of experience with dispersed retailers, suburban slaughterhouses, and food transported by railroad proved disastrous to the public welfare, prompting cities and federal agencies to reclaim this urban civic space.